2011
DOI: 10.1158/1078-0432.ccr-10-2763
|View full text |Cite
|
Sign up to set email alerts
|

Changes in 18F-Fluorodeoxyglucose and 18F-Fluorodeoxythymidine Positron Emission Tomography Imaging in Patients with Non–Small Cell Lung Cancer Treated with Erlotinib

Abstract: Purpose: Assessing clinical activity of molecularly targeted anticancer agents, especially in the absence of tumor shrinkage, is challenging. To evaluate on-treatment 18F-fluorodeoxyglucose (FDG) and/or 18F-fluorodeoxythymidine (FLT) positron emission tomography (PET) for this purpose, we conducted a prospective multicenter trial assessing PET response rates and associations with progression-free (PFS) and overall survival (OS) in 2nd/3rd-line non-small-cell lung cancer patients treated with erlotinib.Experime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 39 publications
(53 reference statements)
9
88
1
Order By: Relevance
“…Therefore, a proportion of patients who benefit from erlotinib treatment without detectable genetic mutations might be identified by early 18 F-FDG PET (8). Similar results were obtained by Mileshkin et al (9), for whom best results were obtained for 18 F-FDG PET after 2 wk of erlotinib treatment in pretreated lung cancer patients.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Therefore, a proportion of patients who benefit from erlotinib treatment without detectable genetic mutations might be identified by early 18 F-FDG PET (8). Similar results were obtained by Mileshkin et al (9), for whom best results were obtained for 18 F-FDG PET after 2 wk of erlotinib treatment in pretreated lung cancer patients.…”
Section: Discussionsupporting
confidence: 70%
“…Because only a few patients show any clinical benefit from erlotinib therapy, identification of the subgroup most likely to respond is a matter of pressing clinical importance to avoid ineffective treatment. 18 F-FDG PET has proven capable of predicting response to therapy with molecularly targeted agents (5)(6)(7)(8)(9). Preclinical models have shown the power of 39-deoxy-39- 18 F-fluorothymidine ( 18 F-FLT) PET to monitor early effects of the tyrosine kinase inhibitor erlotinib (10), and clinical studies have suggested that 18 F-FLT might predict response to both chemotherapy and molecularly targeted drugs (11,12).…”
mentioning
confidence: 99%
“…All the seven studies included were prospective. In two studies, the study population underwent PET and PET/CT (13,25) and PET alone in the remaining studies (8,10,(19)(20)(21). The dose of FDG or FLT ranged considerably across the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in PET features for TKI response assessment and survival prediction have been evaluated in numerous previous studies. However, primarily SUV parameters (SUV peak , SUV max ) have been investigated for outcome prediction, e.g., in NSCLC treated with the TKI erlotinib [29][30][31]. Cook et al reported on heterogeneity assessment in NSCLC treated with the same TKI and the change of first-order parameters were correlated with survival [19].…”
Section: Discussionmentioning
confidence: 99%